2022
DOI: 10.1149/1945-7111/ac4f21
|View full text |Cite
|
Sign up to set email alerts
|

Research on State of Health for the Series Battery Module Based on the Weibull Distribution

Abstract: The state of health (SOH) of a battery module is an important parameter in the battery management system. Accurately grasping the SOH of the battery module can provide the basis for its detection and diagnosis. Here, the series battery module SOH is taken as the research object. Based on the characteristics of the series battery module, a two-parameter Weibull distribution is selected as the module failure data distribution form and then the reliability function of the Weibull distribution is linearized and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This paper uses the shape parameter and scale parameter according to Zhao et al [47], and we have since taken assumptions that allow the progression of this paper. By making assumptions, it is possible to narrow down the subject area; at the same time, this also reduces the causes of failure for a battery system to the cause space considered in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper uses the shape parameter and scale parameter according to Zhao et al [47], and we have since taken assumptions that allow the progression of this paper. By making assumptions, it is possible to narrow down the subject area; at the same time, this also reduces the causes of failure for a battery system to the cause space considered in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Typical battery systems in BEVs have been designed to introduce modularity in the battery system, meaning that cells are connected in a module, and modules subsequently are configured to form a battery pack. To provide context, Zhao et al [47] carried out the analysis on the premise of an electric vehicle battery module. In this paper, the barrel effects of a 1P96S-configurated battery module were analyzed.…”
Section: Weibull Parameter Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test data was further imported into SPSS for analysis. It could be found that the five data items all obey the normal distribution with a significance level of 0.05 under the single-sample K-S test [29] . From this, the average value and floating deviation of different material floating speeds are also obtained.…”
Section: Materials Suspension Velocity Measurementmentioning
confidence: 98%
“…However, since these fault mechanisms occur inside the battery cell, the evaluation of pack or module level is challenging. Nevertheless, very recent research exists, such as by Kampker et al [40], Zhao et al [42], or Xing [43], using statistical models to study battery health and predict failure in different circumstances. For this purpose, the Weibull distribution as well as principal component analysis and improved Gaussian process regression are used.…”
Section: Formulation Of a Solution For Overcoming Second-life Challengesmentioning
confidence: 99%